ChemInform Abstract: Understanding Co‐Mo Catalyzed Ammonia Decomposition: Influence of Calcination Atmosphere and Identification of Active Phase. Issue 19 (21st April 2016) - Duan, Xuezhi; Ji, Jian; Yan, Xiaodong; Qian, Gang; Chen, De; Zhou, Xinggui
Abstract: Co(en)3 MoO4 as an NH3 decomposition catalyst precursor is calcined in argon or air (600 °C, 3 h) and then reduced in pure H2 (600 °C, 3 h).